The incidence of cash for clunkers: An analysis of the 2009 car scrappage scheme in Germany - Ashok Kaul; Gregor Pfeifer; Stefan Witte (University of Zurich, Department of Economics, 2012)
Governments all over the world have invested tens of billions of dollars in car scrappage programs to fuel the economy in 2009. We investigate the German case using a unique micro transaction dataset covering the years 2007 to 2010. Our focus is on the incidence of the subsidy, i.e., we ask how much of the exteuro 2,500 buyer subsidy is captured by the supply-side through an increase in selling prices. Using regression analysis, we find that average prices in fact decreased for subsidized buyers in comparison to non-subsidized ones, suggesting that eventually subsidized customers benefitted by more than the subsidy amount. However, the incidence was heterogeneous across price segments. Subsidized buyers of cheap cars paid more than comparable buyers who did not receive the subsidy, e.g. for cars of exteuro 12,000 car dealers reaped about 8% of the scrappage prime. The opposite was true for more expensive cars, e.g. subsidized buyers of cars of exteuro 32,000 were granted an extra discount of about exteuro 1,100. For cars priced about exteuro 18,000, we find no price discrimination, i.e., in this price segment consumers fully captured the transfer. Our results can be explained by optimizing behavior on the supply-side both in the lower and upper price segments. The results are extremely robust to extensive sensitivity checks.
Keywords: H22; D12; L62; 330; Cash-for-Clunkers; scrappage scheme; incidence; subsidy; pricing; Subvention; Kraftfahrzeugindustrie; Ökonomischer Anreiz; Konsumentenverhalten; Kraftfahrzeug; Preisdifferenzierung; Deutschland